Does Europe need a health union? - Anne Bucher (Bruegel, 2022)
Health outcomes in the European Union are good by international standards, even compared to other developed economies, and improved continuously before COVID-19. This reflects the alignment of the objectives of improving health and wellbeing with the overall socio-economic objective of prosperity, and suggests that a radical overhaul of EU health policy is not needed. However, the EU could benefit from closer integration in some areas and be more effective in delivering a high level of health protection. Action could be taken in the following areas: The European Commission's November 2020 Health Union package to increase resilience to cross-border health threats is ambitious, in particular with the establishment of the Health Emergency Response Authority, which extends the scope of cooperation in health emergencies. The EU should pursue further the Health Union approach to address cross-border externalities and enhance health security. It could, for instance, do more to tackle anti-microbial resistance, or define minimum requirements for the resilience of health systems. For non-communicable diseases, the EU should tap the economies of scale of research and knowledge organised at EU level, and put in place systems for the surveillance of non-communicable diseases and consolidation of scientific knowledge. This could be achieved through an extension to non-communicable diseases of the European Centre for Disease Prevention and Control mandate. The "Health in all Policies" principle is a key channel to deliver good health outcomes at EU level. EU scientific agencies provide health risk assessments in a number of areas, but the EU should better organise, coordinate and consolidate the scientific knowledge that underpins health-protection measures in sectoral legislation, and should more systematically apply better regulation rules to the health impacts of EU policies. The EU should support the digital transformation of health systems and set high targets for the European Health Data Space initiative, which is a critical infrastructure for the future of health research, regulation and policymaking. Several non-health EU policy objectives (cohesion policies, European Pillar of Social rights, economic governance) are linked to the performance of health systems. A common understanding on how to measure this performance would inform these policies in a consistent way. Moreover favourable health outcomes in the EU have not reduced health inequalities, which remain high between and within EU countries. Monitoring of health inequalities, including those related to access to and quality of healthcare, should be improved as an initial step.
Keywords: 330; health economics and policy; eu governance; Covid-19